Reduction of COD and Color from Non-Destructive Testing Wastewater Using Persulfate-Based AOPs Method - Bambang Soeswanto; Endang Kusumawati; Luthfi Alfaridzi Setiawan; Muhammad Rizal Firjatulloh (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
PT Collins Aerospace is an aerospace component electroplating company that utilizes Non-Destructive Testing (NDT) in its production process, generating liquid waste containing fluorescent dyes—toxic, persistent, and complex organic compounds with a light green color. The initial Chemical Oxygen Demand (COD) of the wastewater is 2880 mg/L. To treat this, the Advanced Oxidation Processes (AOPs) method was selected for its ability to degrade complex organics into simpler, non-toxic substances like H₂O and CO₂. This study evaluates the impact of persulfate dosage, heating duration, and operating pH on the reduction of COD and color intensity. The parameters tested include persulfate dosages (100, 300, 500 ppm), heating durations (30, 60, 120 minutes), operating pH levels (4, 6, 9), and temperatures (room temperature and 65°C). Results show that the optimal persulfate dosage was 500 ppm, achieving 77.78% COD reduction and 52.5% color removal. The best heating duration was 120 minutes with 88.33% COD reduction and 58.79% color removal, while pH 6 yielded the highest efficiency, with 88.89% COD reduction and 76.13% color removal, resulting in a clear visual appearance. In contrast, treatment at room temperature showed decreased performance, with 61% COD reduction.